2014
DOI: 10.5045/br.2014.49.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Optimal method for early detection of cardiac disorders in thalassemia major patients: magnetic resonance imaging or echocardiography?

Abstract: BackgroundHeart failure resulting from myocardial iron deposition is the most important cause of death in β-thalassemia major (TM) patients. Cardiac T2*magnetic resonance imaging (MRI), echocardiography, and serum ferritin level serve as diagnostic methods for detecting myocardial iron overload. In this study, we aimed to evaluate the relationship between the above-mentioned methods.MethodsT2*MRI and echocardiographic measurement of left ventricular (LV) systolic and diastolic function were performed in 63 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
4
16
1
Order By: Relevance
“…Those normal values could be interpreted as normal cardiac function. This supports the concept that conventional echocardiography is not sufficiently sensitive to pick up cardiac dysfunction and therefore does not permit early intervention [18]. Several studies concluded that tissue Doppler echocardiography was better than conventional echocardiography to distinguish cardiac dysfunction [19,20], and also correlates significantly with cardiac T2* [21].…”
Section: Discussionmentioning
confidence: 52%
“…Those normal values could be interpreted as normal cardiac function. This supports the concept that conventional echocardiography is not sufficiently sensitive to pick up cardiac dysfunction and therefore does not permit early intervention [18]. Several studies concluded that tissue Doppler echocardiography was better than conventional echocardiography to distinguish cardiac dysfunction [19,20], and also correlates significantly with cardiac T2* [21].…”
Section: Discussionmentioning
confidence: 52%
“…TDI has been used to show systolic and diastolic function of the left ventricle for many years. It was reported that myocardial systolic (S m ) and diastolic (E m , A m ) velocities in the basal and middle segments of the left ventricle were lower in patients with BTM in previous studies . This decrease has been higher in patients with T2* <20 ms .…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have reported that tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE) can detect early myocardial dysfunction in BTM patients. STE is a new noninvasive echocardiographic method for the analysis of regional and global myocardial dysfunction . Although STE has been recently started to use in children, the studies evaluating the myocardial function in children with BTM patients with STE are scarce in the literature …”
Section: Introductionmentioning
confidence: 99%
“…Measuring serum ferritin level remains the primary screening test and is still used in monitoring the efficacy of chelation therapy. It has been reported that serum ferritin level greater than 2500 ng/ml is considered an important risk factor for developing ironinduced complications such as liver cirrhosis, heart failure, arrhythmias, impaired growth, and delayed puberty [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%